2001
DOI: 10.1002/er.672
|View full text |Cite
|
Sign up to set email alerts
|

Photogalvanic effect in aqueous Methylene blue nickel mesh systems: Conversion of light into electricity

Abstract: SUMMARYThe photogalvanic e!ect in electrochemical cells, employing aqueous Methylene blue and Fe(II)/Fe(III) couple electrolyte and nickel-mesh electrodes, were experimentally investigated. Five di!erent standard H-cell con"gurations were set-up by modifying the electrolyte. Long-term open-circuit voltage measurements were conducted in order to test the stability of the cells. Light on}o! reproducibility experiments were also carried out during lengthy cell operations. By comparing experimental quantum yield w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Memming [10] and Bhardwaj et al [11] proposed processes for solar energy conversion using photoelectrochemical and chloroplast photoelectrochemical cells, respectively. Bayer et al [12] and Gangotri and Meena [13] have observed the photogalvanic effect in aqueous methylene blue-nickel mesh and oxalic acid-methylene blue systems, respectively. The effect has also reported using heterocyclic dyes [14], rhodamine B-methylene blue and safranine with ascorbic acid as a reductant [15], and azine dye [16] as photosensitizer.…”
Section: Introductionmentioning
confidence: 97%
“…Memming [10] and Bhardwaj et al [11] proposed processes for solar energy conversion using photoelectrochemical and chloroplast photoelectrochemical cells, respectively. Bayer et al [12] and Gangotri and Meena [13] have observed the photogalvanic effect in aqueous methylene blue-nickel mesh and oxalic acid-methylene blue systems, respectively. The effect has also reported using heterocyclic dyes [14], rhodamine B-methylene blue and safranine with ascorbic acid as a reductant [15], and azine dye [16] as photosensitizer.…”
Section: Introductionmentioning
confidence: 97%
“…Later on, Murthy et al [5], Rohatgi Mukherjee et al [6], Folcher and Paris [7], Alfredo et al [8], Pan et al [9], Dube et al [10], Jana and Bhowmik [11], Bayer et al [12], Matsumoto et al [13] and Shiroishi et al [14] have studied some interesting photogalvanic systems. Bisquert et al [15] have reviewed the physical-chemical principles of dye-sensitized solar cells, whereas Meyer [16] has presented the molecular approaches to solar energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Later, many scientists have put their utmost efforts into solar energy conversion and storage in photogalvanic cells. Among these prominent researchers, Bayer et al (2001) have studied photogalvanic effect in an aqueous methylene blue nickel mesh system, and Olea et al (1990) have studied electron transfer via organic dyes for solar energy conversion. Eisenberg and Silverman (1961) and Mukhopadhyaya and Bhowmik (1992) have studied photoelectrochemical cells.…”
Section: Introductionmentioning
confidence: 99%